Growth response and nutritive value of Azolla and Alternanthera incorporated pelleted feeds on fingerlings of Cyprinus carpio var. communis: a preliminary study - Suresh, V R; Mandal, B K (Indian Journal of Fisheries, 2011)
A 40 day feeding experiment was conducted under laboratory conditions to determine the suitability of dried aquatic fern Azolla and marshy weed Alternanthera philazeroides as ingredients in pelleted feed for a freshwater fish Cyprinus carpio var. communis. A conventional diet (Fl) made of rice bran and mustard oil cake (1:1) was used as control against four diets (F2 to F5) incorporated with different levels of Azolla, Alternanthera, rice bran and mustard oil cake. Better weight gain, percentage growth and specific growth rate were obtained with Fl (3.8Â±1.1 g, 52.78% and 0.81% respectively), followed by F2 (3.4Â±0.4 g, 50.75% and 0.77% respectively). Feed utilization and digestibility parameters were also better with Fl, followed by F2. Although the conventional feed Fl produced higher growth and low FCR, it appeared possible to incorporate dried Azolla and Alternanthera in supplementary feed for the fish